Geoenvironmental problem s in the polje of the southern Apennines: The example of the Forino plain (Campania Region) - Santo, A.; Liguori, M; Aquino, S.; Galasso, M. (Alpine and Mediterranean Quaternary, 2023)
This paper deals with the geo-environmental problems of the Apenninic polje related to the human activity. The studied area is a typical structural polje (Forino basin) located in the carbonatic massif of the Sarno mountains, in the Campania region. The karst plain is located at about 400 metres a.s.l. and it is drained by the ponor of Celzi, in the eastern sector of the plain; all the area is interested by an intense agriculture practice and is partially covered by the town of Forino. The stratigraphical analysis of the filling deposits of the polje, which are mainly pyroclastic fall deposits interlayered with lacustrine silts and clays, together with the geomorphological, hydrogeological and hydrogeochemical study of the area, allowed us to reconstruct the general outline of the underground hydric circulation . In particular, tracing tests carried out on the ponor of Celzi have shown its relation with the basal spring of Labso. Moreover the monitoring of the main springs of the area has shown their state of pollution, due to the immission of the Forino town sewer system in the ponor and to the notable use, for the agriculture practice, of nitrogeneous fertilizers.The study has also displayed that the agriculture practice could be responsible for the increasing of the flooding phenomena in the polje, registered in the last years. The Forino basin is thus a very clear example of how delicate is the geo-environmental equilibrium of the polje and shows that a correct land managment in this area cannot leave out of consideration a multidisciplinary study approach.